The significance of anterior prostate lesions on multiparametric magnetic resonance imaging in African-American men - Kongnyuy, Michael (Urol Oncol, 2016)
INTRODUCTION: African-American (AA) men tend to harbor high-risk prostate cancer (PCa) and exhibit worse outcomes when compared to other groups. It has been postulated that AA men may harbor more anterior prostate lesions (APLs) that are undersampled by the standard transrectal ultrasound guided-biopsy (SBx), potentially resulting in greater degree of Gleason score (GS) upgrading at radical prostatectomy. We aimed to evaluate the detection rate of anterior PCa significance of APLs in AA men on multiparametric magnetic resonance imaging (mpMRI) and compare it to a matched cohort of White/Other (W/O) men. MATERIALS AND METHODS: A review of 1,267 men who had an mpMRI with suspicious prostate lesions and who underwent magnetic resonance transrectal ultrasound fusion-guided biopsy (FBx) with concurrent SBx in the same biopsy session was performed. All AA men were matched to a control group of W/O using a 1:1 propensity score-matching algorithm with age, prostate-specific antigen, and prostate volume as matching variables. Logistic regression analysis was used to determine predictors of APLs in AA men. RESULTS: Of the 195 AA men who underwent mpMRI, 93 (47.7%) men had a total of 109 APLs. Prior negative SBx was associated with the presence of APLs in AA men (Odds ratio = 1.81; 95% CI: 1.03–3.20; P = 0.04). On multivariate logistic regression analysis, smaller prostate (P = 0.001) and rising prostate-specific antigen (P = 0.007) were independent predictors of cancer-positive APLs in AA men. Comparative analysis of AA (93/195, 47.7%) vs. W/O (100/194, 52%) showed no difference in the rates of APLs (P = 0.44) or in cancer detection rate within those lesions or the distribution of GS within those cancers (P = 0.63) despite an overall higher cancer detection rate in AA men (AA: 124/195 [63.6%] vs. W/O: 97/194 [50.0%], P = 0.007). In cases where APLs were positive for PCa on FBx, the GS of APL was equal to the highest GS of the entire gland in 82.9% (29/35) and 90.9% (30/33) of the time in AA and W/O men, respectively. CONCLUSION: Cancer-positive APLs represented the highest risk GS in most cases. AA men with prior negative SBx are twice as likely to harbor a concerning APL. In our cohort, AA and W/O men had comparable rates of APLs on mpMRI. Thus, differences in APLs do not explain the higher risk of AA men for deahth due to PCa. However, targeting of APLs via FBx can clinically improve PCa risk stratification and guide appropriate treatment options.